(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article explores the journey from being a nervous novice to becoming a confident communicator in public speaking. It discusses the importance of developing effective communication skills, strategies for overcoming nervousness, and practical tips for honing public speaking abilities through practice and feedback.